Novel TRPV4 variant causes a severe form of metatropic dysplasia. Issue 9 (20th July 2018) - Graversen, Lise; Haagerup, Annette; Andersen, Brian N.; Petersen, Karin K.; Gjørup, Vibike; Gudmundsdottir, Gudrun; Vogel, Ida; Gregersen, Pernille A.
Key Clinical Message: We present a girl born with a frontal bossing, short neck, bell‐shaped thorax, short limbs with prominent joints, and a tail‐like coccygeal appendage. Genetic screening of TRPV4 identified a novel de novo heterozygous missense variant. We believe the variant causes the severe form of metatropic dysplasia in this patient. Abstract : International collaboration increases the chance of diagnosing rare skeletal dysplasias. We present a girl where metatropic dysplasia was suspected immediately after birth with the help of the Skeletal Dysplasia Network and was genetically confirmed immediately after birth. Early diagnosis facilitates the management of very complex patients.